1983
DOI: 10.2190/kanj-0j0v-c49l-8q7w
|View full text |Cite
|
Sign up to set email alerts
|

Normative Evaluations of Suicide and Death: A Cross-Generational Study

Abstract: Attitudes toward suicide and death across two intra-familial generations were investigated to gain a better understanding of possible causal factors underlying increasing suicide rates among the young. Cultural and subcultural normative evaluations of suicide and death represent important variables in an individual's decision to choose the suicidal option. Thus, the reported increase in youth suicide rates may be a function of more “accepting” attitudes by today's youth toward suicide and death. The investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…Young people are thought to be particularly susceptible to emulating suicidal behaviour of their peers [ 19 ], and this is thought to explain a number of well-publicised suicide clusters [ 20 , 21 ]. There is also evidence that young people are more likely than their elders to hold accepting views towards suicide [ 22 ], regarding it as a means of expressing despair [ 23 ]. Adolescents and young adults who most strongly believe that it is acceptable to end one’s life are more likely to make a suicide plan than those who do not have such beliefs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Young people are thought to be particularly susceptible to emulating suicidal behaviour of their peers [ 19 ], and this is thought to explain a number of well-publicised suicide clusters [ 20 , 21 ]. There is also evidence that young people are more likely than their elders to hold accepting views towards suicide [ 22 ], regarding it as a means of expressing despair [ 23 ]. Adolescents and young adults who most strongly believe that it is acceptable to end one’s life are more likely to make a suicide plan than those who do not have such beliefs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of attitudes in directing social behavior (Eagly & Chaiken, 1993), few studies have attended to the relation between adolescents' and young adults' attitudes toward suicidal behavior and their own suicidality (Goldsmith et al, 2002). Increased societal acceptance of anomic suicide has been related to a rise in suicidal behavior in a Canadian sample of 12th graders (Boldt, 1982), but the extent to which racial differences in suicidal behavior are related to attitudes toward suicide have not been examined. Several studies have compared suicidal to nonsuicidal youth and found the former to be more accepting of their own suicidal behavior and that of others (Butler, Novy, Kagan, & Gates, 1994; De Wilde, Keinhorst, Diekstra, & Wolters, 1993); another recent study found that an approving attitude toward suicide was correlated with a higher level of suicidal ideation (Stein, Brom, Elizur, & Witztum, 1998).…”
mentioning
confidence: 99%
“…Boldt (1987) discussed the possibility that the changing meanings attributed to suicide in our culture is related to the increase in youth suicide rates. In his own research (Boldt, 1982), he compared attitudes toward suicide of high school students and their parents. He found that the teen agers consistently differed from their parents, in a pro-suicide direction.…”
Section: Friendsmentioning
confidence: 99%